2019
DOI: 10.1128/mra.01487-18
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Phascolarctobacterium faecium JCM 30894, a Succinate-Utilizing Bacterium Isolated from Human Feces

Abstract: Phascolarctobacterium faecium is an anaerobic microbe known as a member of the human gut microbiome. Here, we report the complete genome sequence of Phascolarctobacterium faecium JCM 30894 and the elucidation of the mechanism for utilization of succinate by this bacterium based on the genome analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 10 publications
0
31
0
Order By: Relevance
“…Propionate producers Eubacterium siraeum, Ruminococcus bromii, and Blautia obeum, also showed little drop in abundance during 12 months of cryopreservation. Among most abundant butyrate and/or propionate producing bacteria identified in our study, only Phascolarctobacterium faecium, which is a propionate producer (Ogata et al, 2019), showed >50% reduction (56%) in the relative abundance in the first 12 months of cryopreservation. Our results suggest that members of the phylum Firmicutes better support stress conditions and thus would have better chances of survival in the FMT recipients.…”
Section: Discussionmentioning
confidence: 65%
“…Propionate producers Eubacterium siraeum, Ruminococcus bromii, and Blautia obeum, also showed little drop in abundance during 12 months of cryopreservation. Among most abundant butyrate and/or propionate producing bacteria identified in our study, only Phascolarctobacterium faecium, which is a propionate producer (Ogata et al, 2019), showed >50% reduction (56%) in the relative abundance in the first 12 months of cryopreservation. Our results suggest that members of the phylum Firmicutes better support stress conditions and thus would have better chances of survival in the FMT recipients.…”
Section: Discussionmentioning
confidence: 65%
“…This pathway is also present in Phascolarctobacterium spp. (Ogata et al, 2019; Reichardt et al, 2014). However, due to the lack of fumarate reductase, it is presumed that P .…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the lack of fumarate reductase, it is presumed that P . faecium JCM 30894 is unable to produce succinate, a key metabolite of the succinate pathway (Ogata et al, 2019). Therefore, co‐existence with succinate‐producing bacteria, such as Bacteroides , is essential for Phascolarctobacterium spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After 2 to 4 days of incubation at 37°C under a H 2 -CO 2 -N 2 (1:1:8 [vol/vol/vol]) gas mixture, strain CBH12S (ϭ JCM 30893) was isolated. Genomic DNA extraction, sequencing with the Illumina MiSeq and PacBio Sequel platforms, quality checking of reads, de novo hybrid assembly of both reads, and quality checking of the genome were performed as previously described (5), and default parameters were used for all software unless otherwise specified. We obtained a total of 278,916,914 bases from 467,638 filter-passed Illumina paired reads with an average length of 298.2 bp, and a total of 676,968,912 bases from 43,760 filter-passed PacBio reads with an average length of 15,470 bp.…”
mentioning
confidence: 99%